2009
DOI: 10.1016/j.powtec.2009.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanics of granular material response during load reversals: Combined DEM and experimental study

Abstract: ABSTRACT:The use of ideal granular materials with regular, simple geometries (e.g. steel spheres) allows accurate geometrical representation of physical test specimens to be made in DEM simulations. Physical tests on these materials can then be used to validate DEM models and these DEM models can be confidently used to develop insight into the micro-scale interactions driving the macro-scale response observed in the laboratory. A novel approach to simulating triaxial tests with DEM using circumferential period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(36 citation statements)
references
References 12 publications
1
32
0
Order By: Relevance
“…DEM has been often used to model ballast because it can capture the discrete nature of particulate materials (Oda and Iwashita 1999;O'sullivan 2011). DEM can examine the mechanical behaviour of a granular assembly consisting of a collection of arbitrarily shaped discrete particles subjected to quasi-static and dynamic conditions (Lu and McDowell 2008;O'sullivan and Cui 2009;Tutumluer et al 2012). In DEM, the force-displacement law derives the contact force acting on two particles in contact to the relative displacement between them (Itasca 2014).…”
Section: Discrete Element Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…DEM has been often used to model ballast because it can capture the discrete nature of particulate materials (Oda and Iwashita 1999;O'sullivan 2011). DEM can examine the mechanical behaviour of a granular assembly consisting of a collection of arbitrarily shaped discrete particles subjected to quasi-static and dynamic conditions (Lu and McDowell 2008;O'sullivan and Cui 2009;Tutumluer et al 2012). In DEM, the force-displacement law derives the contact force acting on two particles in contact to the relative displacement between them (Itasca 2014).…”
Section: Discrete Element Modellingmentioning
confidence: 99%
“…The discrete element method (DEM) proposed by Cundall and Strack (1979) has been widely used to examine the micromechanical properties of ballast materials (Lim and McDowell 2005;Lobo-Guerrero and Vallejo 2005;Tutumluer et al 2007;Bhandari et al 2009;O'sullivan and Cui 2009;Lobo-Guerrero and Vallejo 2010;Lu and McDowell 2010;Zhang et al 2013;Huang et al 2013;Tutumluer et al 2013;Mishra et al 2014;Indraratna et al 2015;Ngo et al 2015;Qian et al 2015), among others, but most of these numerical studies focused on fresh ballast. McDowell et al (2006) used the discrete element method to model largescale triaxial experiments of ballast aggregates reinforced with geogrids, and concluded that the DEM approach holds much promise as a tool for investigating granular aggregate assemblies.…”
Section: Introductionmentioning
confidence: 99%
“…DEM is employed to model quasi-static deformation of soils/ granular materials, e.g. triaxial tests, confined compression and box shear tests [30][31][32]. It is also employed to study aspects like particle packing, and dynamic problems like flow of granular media through hoppers or conveyer systems [33][34][35][36].…”
Section: Discrete Approachmentioning
confidence: 99%
“…Discrete element method (DEM), introduced by Cundall and Strack [4], provided a framework to investigate the independent interaction of individual particles and permitted acquiring particle-level measurements including contact forces, which are impossible to obtain using conventional experimental techniques [5]. DEM's applicability for modeling engineering applications is limited, however, by its inability to represent real particle morphology and the expensive computational time necessary for large specimens.…”
Section: Introductionmentioning
confidence: 99%